Impact of patient and disease characteristics on the efficacy and safety of eluxadoline for IBS-D: a subgroup analysis of phase III trials. (April 2019) - Lacy, Brian E.; Harris, Lucinda A.; Chang, Lin; Lucak, Susan; Gutman, Catherine; Dove, Leonard S.; Covington, Paul S.; Lembo, Anthony
Background: Irritable bowel syndrome with diarrhea (IBS-D) is a prevalent gastrointestinal (GI) disorder with a varied presentation, often overlapping with other GI and non-GI disorders. Eluxadoline is a locally active mixed µ- and κ-opioid receptor agonist and δ-opioid receptor antagonist approved for the treatment of IBS-D in adults. As IBS-D is a heterogeneous disease, factors such as patient demographics, symptom severity, and symptom pattern history can potentially inform treatment selection. Methods: Here, we report additional prospectively planned analyses of two large double-blind, placebo-controlled studies (IBS-3001 and IBS-3002) enrolling patients meeting Rome III criteria for IBS-D. Patients were randomized 1:1:1 to receive placebo or eluxadoline 75 mg or 100 mg twice daily. Efficacy (abdominal pain, stool consistency, and composite, simultaneous improvement in both) and safety were assessed for prospectively defined patient subgroups stratified by age, sex, race, presence of comorbidities, and baseline disease characteristics. Results: Across all age, sex, race, comorbidity, and disease characteristic subgroups, a greater proportion of patients were composite responders with both eluxadoline doses as compared with placebo, including patients with a history of depression or a history of gastroesophageal reflux disease. Among patients aged ⩾65 years, a greater proportion of patients receiving eluxadoline 75 mg were composite, abdominal pain, and stool consistency responders compared with those receiving 100 mg. The proportion of patients with at least one adverse event was slightly higher in patients aged ⩾65 years and also in female patients. Conclusions: This analysis suggests that eluxadoline is effective in treating IBS-D across a range of commonly encountered patient types. In contrast to the overall population, patients aged ⩾65 years demonstrated a greater proportion of responders at the lower approved 75 mg eluxadoline dose.